TI_GERICHTE 11.2007.191 vom 17. Oktober 2008 , Rivendicazione di proprietà: misure provvisionali Esecuzione civile - TI Tribunale d'appello (2008)
Rivendicazione di proprietà: misure provvisionali Esecuzione civile